PENERAPAN KONSEP WALKABILITY DI KAWASAN ALUN-ALUN KOTA MALANG - Imma Widyawati Agustin (Jurnal Pengembangan Kota, 2017)
City center plaza of Malang (Alun-alun Merdeka) is a commercial area and public open space that attracts and encourages the movement of the community including the pedestrian in Malang city. A high pedestrian movement should be balanced with the availability of adequate facilities and infrastructure, particularly the pedestrian ways that can provide comfort, safety and sociability for pedestrians or called as the walkable pedestrian ways. The main purpose of the research is providing an input for pedestrian ways planning based on the concept of walkability, particularly for a public square in Malang. This research used guidelines from Permen PU number 03/PRT/M/2014 to identify the level of service of pedestrian-ways and the standard of the US Department Health and Human Service to find out the index of walkability, and Importance Performance Analysis (IPA) to know the priority improvements of pedestrian-ways. The results showed that Merdeka Selatan street and Merdeka Timur street has the worst level of service is B on the weekday while on the weekend, Merdeka Timur street has the worst level of service is E. Pedestrian-ways on Merdeka street has the index of walkability is quite walkable with the score of 40-69. The planning of restructuring pedestrian ways on the City center plaza of Malang City (Alun-alun Merdeka) has different priority for each corridor, in general the priority of restructuring is adding lighting trash bin, as well as the disability paths.